Implementation Of Learning Cycle 5E Model Assisted With Computer Simulation To Increase Physical Learning Outcome In Student Class VII SMPN 1 Torue - Wiyandari, Ni Putu; Hatibe, Amiruddin; Saehana, Sahrul (Berkala Ilmiah Pendidikan Fisika, 2017)
This study aims to improve students physics learning outcomes of class VII SMP Negeri 1 Torue by using learning cycle 5E model assisted with computer simulation. Design of this action research methods follows the model of Kemmis and Mc. Taggart and it was done in two cycles. Each cycle consists of four stages of planning, implementation of action, observation and reflection. The subjects of this study are students of class VIIE SMP Negeri 1 Torue which amounted to 24 students. They consist of 13 male and 11 female students. The research material for cycle I is âform of substanceâ and cycle II materil is âexpansionâ. In this study, data were collected through observation and student activity, test of action result and interviews. On the evaluation of cycle I, we obtained classical completeness about 65.21% and classical absorption was about 68.26%. Student activity is in âenough categoryâ with percentage about 78,25%. Teacher activity is in âgood categoryâ with 85% percentage. In the second cycle, we obtained learning classical completeness about 86.96% and classical absorption about 81.96%. Student activity and teacher activity are in âvery good categoriesâ with percentages of 90% and 96.67%, respectively. It was concluded that the implementation of 5E learning cycle learning model assisted computer simulation can improve student learning result of VIIE grade SMP Negeri 1 Torue.